2021
DOI: 10.24002/jts.v16i1.4216
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Perubahan Tata Guna Lahan Terhadap Debit Puncak Di Sub Das Talang Kabupaten Jember

Abstract: Sub DAS Talang merupakan bagian dari DAS Mayang yang merupakan salah satu daerah aliran sungai yang berada di Kabupaten Jember. Meningkatnya kebutuhan manusia terhadap tempat tinggal menyebabkan perubahan tata guna lahan dari daerah resapan menjadi pemukiman. Sehingga air hujan tidak dapat meresap ke dalam tanah dan menjadi aliran  permukaan dan menyebabkan debit yang dihasilkan meningkat. Maka dari itu dilakukan  klasifikasi citra landsat 7 & 8 menggunakan program ERR Mapper & ArcGIS untuk mengetahui … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This causes an increase in discharge in a watershed, so an analysis is needed regarding the increase in discharge that occurs in that watershed. The method used in calculating the peak discharge is the HSS Snyder method, which is then analyzed for correlation using the regression equation to obtain the value of the correlation coefficient (Putri, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This causes an increase in discharge in a watershed, so an analysis is needed regarding the increase in discharge that occurs in that watershed. The method used in calculating the peak discharge is the HSS Snyder method, which is then analyzed for correlation using the regression equation to obtain the value of the correlation coefficient (Putri, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The method used to analyze peak discharge is Snyder SUH. Correlation analysis to obtain a more appropriate peak discharge value (Putri, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study found that flood discharge increased along with the LULC change from 1990-2009. The LULC change in Talang Watershed, Jember District (East Java Province) increased gradually by about 67.48% from 2009-2018 based on [3] study. [4] studied the flood discharge resulting from LULC change at Siak Watershed, Riau Province.…”
Section: Introductionmentioning
confidence: 99%